Предмет: Алгебра,
автор: Vonka2
(((sin (П - 3a) - cos ((3П/2)+a))*cos(a - (5П/ 2))) / (1 + cos (П - 2a))) = cos 2a
Ответы
Автор ответа:
2
sin (π - 3a)=sin3a
cos ((3π/2)+a))=sina
cos(a - (5π/ 2))=cos((5π/2)-a)=sina
cos (π - 2a) = -cos2a
1+cos(π-2a)=1-cos2a=2sin²a
=((sin3a-sina)·sina)/(2sin²a)=(2sina·cos2a)/(2sina)=cos2a
Похожие вопросы
Предмет: Русский язык,
автор: nick19762
Предмет: Русский язык,
автор: aramPro
Предмет: Английский язык,
автор: гомельская
Предмет: Алгебра,
автор: Аноним
Предмет: Физика,
автор: Makedonskiy228